Electrocardiographic recognition of life-threatening hyperkalaemia: the hyperkalaemic Brugada sign. Issue 9 (August 2019) - McNeill, Holly; Isles, Chris
Lesson: Consider life-threatening hyperkalaemia if the ECG shows high take-off with coved ST segment elevation and negative T wave in lead V1 superimposed on other ECG signs of hyperkalaemia and treat with calcium gluconate while waiting for blood chemistry results.